HEALTH PROTOCOL CERTIFICATION FOR TOURISM BUSINESS DUE TO COVID-19 OUTBREAKS IN BALI - Syahrin, Alfi (UI Scholars Hub, 2021)
The World Health Organization on March 11, 2020 declared the Covid-19 outbreak a global pandemic. Tourism is one of the sectors most affected. The number of foreign tourist visits to Indonesia has decreased significantly, namely 64.11% in March 2020 when compared to March 2019. To restore this condition, it is very necessary to prevent the spread of Covid-19 and carry out certification for tourism business actors. The data for analysis was collected by searching for words that are closely related to the topic of research on the Google Search Engine to obtain the website followed by visiting the intended website that has the necessary data. Descriptive analysis used to describe data based on the number and type. There are three research questions to be answered: (1) What are the efforts to prevent the spread of Covid-19? (2) Where is the distribution of tourism businesses that are certified by health protocols? (3) What percentage of the total number of certified tourism businesses out of 1,000 are targeted? More than 87.5% of certified tourism business actors obtained and a map of the distribution of the number and types of certified tourism businesses in Bali is compiled.